Transnational labour governance in hazelnut value chain: farmers and seasonal migrant workers at the nexus of market and politics in Turkey - Sinem Kavak (Frontiers in Sustainable Food Systems, 2025)
This article combines insights from two emerging literatures on transnational private regulation: the grounding perspective and politics and power in global value chains. Drawing on a case study conducted in Turkey, it examines political economy of voluntary sustainability standards in hazelnut production, a critical but overlooked part of the chocolate value chain with no shortage of human rights scandals. Focusing on smallholders and migrant workers, it problematizes the decent work programmes of transnational private governance systems. In Turkey, the agricultural labour market is ethnically segregated, and agricultural work is carried out by seasonal migrant workers belonging to the country’s Kurdish and Arab minorities and refugees, mainly from Syria. Decent work programmes focus on these workers. Through an analysis of the roles of actors (the state, corporations, exporters, local merchants, producers, workers, and third-party certifiers) in the financialized hazelnut market, I demonstrate that farmers and workers cannot sufficiently benefit from transnational private governance programmes due to political power dynamics, market structure, and price volatility at the nation-state level. I argue that any effort to assess the impact of private-led social justice schemes in food production must include a thorough analysis of country conditions, societal conflicts, power asymmetries, and the structure of the commodity market.